The spitzer extragalactic representative volume survey (SERVS): Survey definition and goals - Mauduit, J.; Lacy, M.; Farrah, D.; Surace, J.; Jarvis, M.; Oliver, S.; Maraston, C.; Vaccari, M.; Marchetti, L.; Zeimann, G.; Gonzáles-Solares, E.; Pforr, J.; et al. (2012)
We present the Spitzer Extragalactic Representative Volume Survey (SERVS), an 18 deg2 medium-deep survey at 3.6 and 4.5 μm with the postcryogenic Spitzer Space Telescope to ≈2 μJy (AB = 23.1) depth of five highly observed astronomical fields (ELAIS-N1, ELAIS-S1, Lockman Hole, Chandra Deep Field South, and XMM-LSS). SERVS is designed to enable the study of galaxy evolution as a function of environment from z ~ 5 to the present day and is the first extragalactic survey that is both large enough and deep enough to put rare objects such as luminous quasars and galaxy clusters at z gsim 1 into their cosmological context. SERVS is designed to overlap with several key surveys at optical, near- through far-infrared, submillimeter, and radio wavelengths to provide an unprecedented view of the formation and evolution of massive galaxies. In this article, we discuss the SERVS survey design, the data processing flow from image reduction and mosaicking to catalogs, and coverage of ancillary data from other surveys in the SERVS fields. We also highlight a variety of early science results from the survey.